Gestational diabetes impacts fetal precursor cell responses with potential consequences for offspring. (27th December 2019) - Algaba‐Chueca, Francisco; Maymó‐Masip, Elsa; Ejarque, Miriam; Ballesteros, Mónica; Llauradó, Gemma; López, Carlos; Guarque, Albert; Serena, Carolina; Martínez‐Guasch, Laia; Gutiérrez, Cristina; Bosch, Ramón; Vendrell, Joan; et al.
Abstract: Fetal programming has been proposed as a key mechanism underlying the association between intrauterine exposure to maternal diabetes and negative health outcomes in offspring. To determine whether gestational diabetes mellitus (GDM) might leave an imprint in fetal precursors of the amniotic membrane and whether it might be related to adverse outcomes in offspring, a prospective case‐control study was conducted, in which amniotic mesenchymal stem cells (AMSCs) and resident macrophages were isolated from pregnant patients, with either GDM or normal glucose tolerance, scheduled for cesarean section. After characterization, functional characteristics of AMSCs were analyzed and correlated with anthropometrical and clinical variables from both mother and offspring. GDM‐derived AMSCs displayed an impaired proliferation and osteogenic potential when compared with control cells, accompanied by superior invasive and chemotactic capacity. The expression of genes involved in the inflammatory response ( TNFα, MCP‐1, CD40, and CTSS ) was upregulated in GDM‐derived AMSCs, whereas anti‐inflammatory IL‐33 was downregulated. Macrophages isolated from the amniotic membrane of GDM mothers consistently showed higher expression of MCP‐1 as well. In vitro studies in which AMSCs from healthy control women were exposed to hyperglycemia, hyperinsulinemia, and palmitic acid confirmed these results. Finally, genes involved in the inflammatory response were associated with maternal insulin sensitivity and prepregnancy body mass index, as well as with fetal metabolic parameters. These results suggest that the GDM environment could program stem cells and subsequently favor metabolic dysfunction later in life. Fetal adaptive programming in the setting of GDM might have a direct negative impact on insulin resistance of offspring. Abstract :